The Rise of Ecopedagogy in Elementary Science: A Five-Year Bibliometric Mapping - Septina Rahmawati; Woro Sumarni; Sarwi Sarwi; Sri Wardani; Alwy Ahmed Mohammed (Universitas Muhammadiyah Surakarta, 2026)
Ecopedagogy has gained increasing attention in science education, particularly at the elementary school level, due to the growing need to enhance students' environmental awareness and sustainability literacy. The objective of this study is to analyse research trends and the development of ecopedagogy in elementary science education. The study is based on Scopus-indexed publications from 2020 to 2025. This study employs a bibliometric analysis combined with a systematic literature review approach to map publication trends, journal sources, international collaborations, and country contributions related to ecopedagogy research. The data were analysed using VOSviewer and Biblioshiny to visualise relationships among key concepts. The findings reveal a significant increase in ecopedagogy-related publications, with major contributions from countries such as the United States and China. Furthermore, technology integration and interdisciplinary approaches have emerged as dominant themes in the development of ecopedagogy in science education. This study emphasises the significance of incorporating ecopedagogy as a pedagogical approach within elementary science curricula, particularly through teacher professional development and cross-disciplinary collaboration to promote sustainable education. Future research is recommended to explore empirical implementations and measure their impact on students’ environmental understanding and behavior